2011
DOI: 10.1002/hbm.21383
|View full text |Cite
|
Sign up to set email alerts
|

The role of the left posterior parietal lobule in top‐down modulation on space‐based attention: A transcranial magnetic stimulation study

Abstract: Converging evidence from neuroimaging as well as lesion and transcranial magnetic stimulation (TMS) studies has been obtained for the involvement of right ventral posterior parietal cortex (PPC) in exogenous orienting. However, the contribution of dorsal PPC to attentional orienting, particularly endogenous orienting, is still under debate. In an informative peripheral cueing paradigm, in which the exogenous and endogenous orienting can be studied in relative isolation within a single task, we applied TMS over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 91 publications
2
12
0
Order By: Relevance
“…Our findings indicate that the PPC can nevertheless be fractionated in terms of the subregions that are necessary for particular functional operations in the interplay between WM and attention. For instance, earlier studies have demonstrated that left PPC is involved in endogenous orienting to spatially cued locations (Du, Chen, & Zhou, 2012), but our results extend these findings to specify that left PPC is critical in exerting strategic control over the WM-attention relationship according to trial validity. Stimulating left PPC did not produce a general impact on effects of validity or predictability but, as anticipated, revealed that one of the region’s specific functions is to voluntarily boost the impact of WM content on visual attention when it is known to be helpful.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Our findings indicate that the PPC can nevertheless be fractionated in terms of the subregions that are necessary for particular functional operations in the interplay between WM and attention. For instance, earlier studies have demonstrated that left PPC is involved in endogenous orienting to spatially cued locations (Du, Chen, & Zhou, 2012), but our results extend these findings to specify that left PPC is critical in exerting strategic control over the WM-attention relationship according to trial validity. Stimulating left PPC did not produce a general impact on effects of validity or predictability but, as anticipated, revealed that one of the region’s specific functions is to voluntarily boost the impact of WM content on visual attention when it is known to be helpful.…”
Section: Discussionsupporting
confidence: 83%
“…The more superior and anterior area of the PPC that was stimulated on the right, for instance, corresponds to a region that has been shown, with neuroimaging, to be functionally correlated with activity in the dorsal premotor cortex (Mars et al, 2011), and is activated by the updating of visuo-motor contingencies (Rushworth, Paus, & Sipila, 2001), which aligns with its role here in overcoming WM-matching visual distractors and responding to targets instead. The more inferior and posterior area that was stimulated on the left, however, has been shown to be functionally connected with the parahippocampal gyrus and anterior prefrontal cortex (Mars et al, 2011), and associated with endogenous spatial orienting (Du et al, 2012; Thiel, Zilles, & Fink, 2004), consistent with its role here in strategically attending WM-matching targets. The distinct functional and anatomical connections of the stimulated subcomponents of left and right PPC may underlie their unique contributions to the interaction between WM content and visual attention.…”
Section: Discussionsupporting
confidence: 63%
“…Prior to the start of the experiment each subject underwent an anatomical MRI scan. These images were imported into Brainsight™ TMS Frameless Navigation system (Rogue Research Inc, Montreal, Canada) to allow for online control of coil positioning (Du, Chen, & Zhou, 2012). The stimulus target was the scalp position above the left motor cortex where TMS induced the maximum peak-to-peak MEP amplitude from the right FDI muscle on each session.…”
Section: Methodsmentioning
confidence: 99%
“…Imaging data were collected using a Siemens 3T Trio scanner and a 32 channel head coil located at the Maryland Psychiatric Research Center. The structural images were imported into Brainsight™ TMS Frameless Navigation system (Rogue Research Inc, Montreal, Canada) to allow for online control of precise coil positioning (Du et al 2012). The stimulus target for each participant was the scalp position above the left hemisphere where TMS induced the maximum peak-to-peak MEP amplitude from the right first dorsal interosseous muscle (averaged MNI stereotaxic coordinates: -43, -12, 63).…”
Section: Methodsmentioning
confidence: 99%